2010
DOI: 10.1074/jbc.m110.117234
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Sets of Parallel, In-register β-Strands of β2-Microglobulin in Amyloid Fibrils Revealed by Site-directed Spin Labeling and Chemical Labeling

Abstract: β2-microglobulin (β2m) is a 99-residue protein with an immunoglobulin fold that forms β-sheet-rich amyloid fibrils in dialysis-related amyloidosis. Here the environment and accessibility of side chains within amyloid fibrils formed in vitro from β2m with a long straight morphology are probed by site-directed spin labeling and accessibility to modification with N-ethyl maleimide using 19 site-specific cysteine variants. Continuous wave electron paramagnetic resonance spectroscopy of these fibrils reveals a core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
71
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 54 publications
(111 reference statements)
11
71
0
Order By: Relevance
“…These WL fibrils are formed under different conditions to the amyloid-like fibrils of β 2 m and do not contain a highly ordered cross-β structure, as revealed by EPR, magic angle spinning NMR, and FTIR (29,30,33). Moreover, they exhibit a reduced ability to disrupt cellular function and to induce dye release from liposomes compared with their amyloid-like counterparts (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These WL fibrils are formed under different conditions to the amyloid-like fibrils of β 2 m and do not contain a highly ordered cross-β structure, as revealed by EPR, magic angle spinning NMR, and FTIR (29,30,33). Moreover, they exhibit a reduced ability to disrupt cellular function and to induce dye release from liposomes compared with their amyloid-like counterparts (27).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that these fibrils possess a parallel in register cross-β structure (29,30) assembled into multidomain filaments coiled together, described by cryo-EM (28). These fibrils bind amyloid-specific ligands such as serum amyloid P component with a similar affinity to their ex vivo counterparts (31).…”
mentioning
confidence: 93%
“…Experimental results for Aβ 1-40 (6,8,10,11,13,14), Aβ 1-42 (5, 6, 9), Aβ 10-35 (1, 9), α-synuclein (22), amylin (20,21), β 2 -microglobulin (23,24), Ure2p (27), Sup35 (26), and PrP (28,29) fibrils support the idea that in-register parallel β-sheets might be a universal structural feature of amyloid fibrils when they are formed by full-length peptides and proteins. For HET-s fibrils, a "quasi-in-register" parallel β-sheet structure was also found, with homologous protein segments forming a parallel cross-β motif (48).…”
Section: Discussionmentioning
confidence: 99%
“…Antiparallel β-sheets with odd values of N-M occur in fibrils formed by residues 11-25 of Aβ (Aβ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], where the registry is 17 þ k ↔ 20 − k at pH 7.4 and 17 þ k ↔ 22 − k at pH 2.4 (31). SSNMR spectra of Aβ 11-25 fibrils show sharp lines and single sets of chemical shifts, indicating high symmetry (i.e., one molecule in the asymmetric unit).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation